Evidence of Saffold virus circulation in Italy provided through environmental surveillance. (1st February 2020) - Bonanno Ferraro, G.; Mancini, P.; Veneri, C.; Iaconelli, M.; Suffredini, E.; Brandtner, D.; La Rosa, G.
Abstract: Saffold virus (SAFV) is an emerging human cardiovirus associated with respiratory and gastrointestinal infection, and, more recently, to symptoms related to the endocrine, cardiovascular, and neurological systems. Information about SAFV circulation in Italy is scarce. In order to provide insights into the epidemiology of SAFV in Italy, 141 raw sewage samples collected throughout Italy were tested using broad‐range nested RT‐PCR primers targeting the 5′‐NC region. Seven samples (5·0%) were confirmed as SAFV in samples collected in North, Centre and Southern Italy. Typing was attempted through amplification of the VP1 coding region, using both published and newly designed primers, and one sample was characterized as SAFV‐2. Significance and Impact of the Study: Prevalence, genetic diversity and geographic distribution of SAFV in Italy is currently unknown. This study represents the first detection of SAFV in sewage samples in Italy, suggesting that it is circulating in the population despite lack of clinical reporting. Whether the virus is associated with asymptomatic cases or with undetected gastroenteritis or respiratory illness is unknown. Further studies are needed to investigate on the occurrence and persistence of SAFV in water environments and its waterborne transmission potential.